Accounting Professionals' Perceptions of Ethics Education: Evidence from Turkey - Ali Uyar; Ali Haydar Güngörmüş (Journal of Accounting and Management Information Systems (JAMIS), 2013)
The purpose of this study is to investigate accounting professionals' perceptions of (1) importance of education phases and environmental conditions in development of ethics awareness, (2) approaches in accounting ethics education in university and professional pre-qualification, and (3) coverage of accounting ethics education. Data was collected from public accountants via an online questionnaire during November and December, 2011. The questionnaire was developed based on a review of earlier studies. A total of 219 accountants replied to the survey. The findings demonstrated that most of the respondents (i.e. practicing accountants) have not taken ethics education previously. Secondly, the results provided evidence that all stages of education life, ranging from kindergarten to university, are important and contribute to the development of ethics awareness. Environmental factors are also important in the development of ethics awareness. Giving ethics as a stand-alone course is considered the most appropriate approach in teaching ethics. Responses indicated that "auditing" is the most and only course in which ethics should be taught. Moreover, the respondents approved the inclusion of ethics within various stages of the certified accountancy curriculum.
Keywords: M49; A23; 650; Accounting; accountant; ethics; education; Turkey